Iron-Deficiency in Atopic Diseases: Innate Immune Priming by Allergens and Siderophores - Roth-Walter, Franziska (Frontiers in Allergy, 2022)
Though iron is one of the most abundant elements on earth, about a third of the world’s population are affected by iron-deficiency. Main drivers of iron-deficiency are beside the chronic lack of dietary iron, a hampered uptake-machinery as a result of immune activation. Macrophages are the principal cells distributing iron in the human body with its iron restriction skewing these cells to a more pro-inflammatory state. Consequently, iron-deficiency has a pronounced impact on immune cells, favoring Th2-cell survival, immunoglobulin class-switching and primes mast cells for degranulation. Iron-deficiency during pregnancy increases the risk of atopic diseases in children, while both allergic children and adults are more likely to have anaemia. In contrast, an improved iron status seems to protect against allergy development. Here, the most important interconnections between iron metabolism and allergies, the effect of iron deprivation on distinct immune cell types as well as the pathophysiology in atopic diseases are summarized. Though the main focus will be humans, we also compare them with innate defense and iron sequestration strategies of microbes given particularly attention to catechol-siderophores. Similarly, the defense and nutritional strategies in plants with their inducible systemic acquired resistance by salicylic acid, which further leads to synthesis of flavonoids as well as pathogenesis-related proteins will be elaborated as both are very important for understanding the etiology of allergic diseases. Many allergens, such as lipocalins and the pathogenesis-related proteins, are able to bind iron and either deprive or supply iron to immune cells. Thus, a local induced iron-deficiency will result in immune activation and allergic sensitisation. However, the same proteins such as the whey protein beta-lactoglobulin can also transport this precious micronutrient to the host immune cells (holoBLG) and hinder their activation, promoting tolerance and protecting against allergy. Since 2019, several clinical trials have also been conducted in allergic subjects using holoBLG as a food for special medical purposes, leading to a reduction in the allergic symptom burden. Supplementation with nutrient-carrying lipocalin proteins can circumvent the mucosal block and nourish selectively immune cells, therefore representing a new dietary and causative approach to compensate for functional iron deficiency in allergy sufferers